Sprawiedliwość Syna według Listu do Hebrajczyków - Malina, Artur (Verbum Vitae, 2014)
The study concerns the fi rst mentions of the righteous kingdom and the love of justice in the Letter to the Hebrews. The meaning of the analyzed terms is built by their author on the comparison between Son’s immutability and His superiority to the nature and position of angels (1:8-9). Son’s love of justice is not limited to His passion and death, but is manifested through everything that preceded His anointing as the King of justice. This manifestation makes Him the example of the justice that the Christian are called to exhibit in their lives.